Effects of childhood and adolescence-adulthood respiratory infections in a general population - Paoletti, P; Prediletto, R; Carrozzi, L; Viegi, G; Di Pede, F; Carmignani, G; Mammini, U; Giuntini, C; Lebowitz, MD (The European respiratory journal, 1989)
The role of childhood respiratory infections before 12 yrs of age (CRI) and during adolescence-adulthood (ARI) was studied in a general population sample (n = 3,289), living in an unpolluted area of Northern Italy. The presence of respiratory symptoms and diseases, as well as risk factors for obstructive airways disease (OAD), was assessed by a standardized questionnaire. Forced vital capacity and derived expiratory flows, and single-breath diffusing capacity were measured using computerized instrumentation. There were 1,185 (36.2%) subjects who reported pertussis (PT), 374 (11.4%) recurrent chest colds, pneumonia and croup, singly or in combination, with or without pertussis (CRI), and 1,718 (52.4%) reported no respiratory infections in childhood (NOCRI). Prevalence rates of respiratory symptoms and diseases were significantly higher in subjects of the CRI group in all ages, and in older smokers. Wheeze and attacks of shortness of breath with wheeze were significantly higher in younger nonsmoking subjects with a history of CRI. Respiratory symptoms and diseases were not more prevalent in subjects of the PT group. Prevalence rates of respiratory symptoms and diseases were significantly higher in subjects with a history of ARI, both in smokers and nonsmokers. Lung function parameters adjusted for sex, age and smoking were significantly lower in CRI subjects; PT subjects showed lower values than NOCRI subjects. A significantly higher prevalence rate of ARI was present in subjects who reported CRI, both in smokers and nonsmokers. Subjects with both CRI and ARI showed the highest prevalence of respiratory symptoms and diseases. In addition, they had the lowest lung function values regardless of smoking habit.